A nanoparticle-coated microfluidic chip for automated, non-destructive extraction of encapsulated DNA in data storage. Issue 15 (1st March 2023) - Geng, Chunyang; Liu, Shaoqin; Jiang, Xingyu
Abstract : In this work, we first utilize nanoparticles to yield superhydrophobic surfaces for accurate fluid flow control, and design a CD microfluidic chip integrated with multiplex functions to realize non-destructive information extraction from data DNA. Abstract : DNA data storage based on tubes as physical storage carriers has been developed to solve the problem of the exponential growth of information. Compact disk (CD)-microfluidics that employs centrifugal forces for fluidic manipulation offers an attractive alternative that integrates complex assays onto a miniaturized platform to result in automation for DNA data storage. In this work, we develop a CD microfluidic chip modified with nanoparticles for accurate fluid flow control. The nanoparticle coating turns microchannels into valves or pumps, which reduces the error in fluidic control from 62% to 6%. Based on the nanoparticle coating, the chip integrates demineralization, nucleic acid amplification, and re-mineralization functions for automated, non-destructive information extraction. We prove the functionality of the chip with mineralized DNA data. Compared to purely manual operation and traditional amplification techniques, the microfluidic chip saves human power and time consumption, demonstrating an essential contribution to the development of DNA data storage.